Price Variation and Availability of Free Medicine for Non-communicable Diseases - Devkota, Amrit; Poudel, Anubhav; Koirala, Bhawesh; Baral, Dharanidhar; Gautam, Swotantra; Sharma, Sanjib Kumar (Journal of Nepal Health Research Council, 2018)
Background: Nepal is witnessing rise in non-communicable chronic diseases. Costs of the medicine, availability of the medicine for free in public health sectors and variation of price of medicines may play an important role in the management of chronic disease. The study was undertaken to find out the variation in price of drugs used for treating non communicable diseases among private pharmacies and availability of free essential medicines in public facilities. Methods: Randomly selected 33 public health centers and 13 pharmacies were included for the study. Availability of free essential medicines for treating selected chronic diseases was assessed in public health centers and percentage price variation in various branded drugs used for treating these diseases was assessed at the consumer level. Results: Out of 89 different formulations, variations between maximum and minimum priced brands of more than 100% were observed in 37 formulations and that of > 200% in 22 formulations. Thirty-seven formulations had more than 100% inter-pharmacy variation. The most commonly available free essential medicines was 4 mg salbutamol (88.57%) while the least available free essential drug was levothyroxine 5 mg (9.0%). Conclusions: Considerable variation in prices is seen among similar drugs and in prices of same drug in different pharmacies. These factors may have implications in the management of chronic disease in Nepal offsetting the government’s effort to control chronic diseases. Keywords: Chronic diseases; essential medicines; price variation.